The mediating effects of self-concept on the relationship between parenting styles and young children’s social problem-solving in Türkiye - Ayık, Ahmet; Sezer, Türker; Koçyiğit, Sinan (Frontiers in Psychology, 2025)
The aim of this study was to investigate the associations between parenting styles, young children’s social problem-solving skills, and the mediating role of self-concept in a sample of 200 Turkish preschoolers aged 48–72 months, with an equal distribution of male and female participants. The present study was designed using a cross-sectional survey model in order to achieve the descriptive and predictive aims of the research. Data were collected through individual sessions with the children. During these sessions, the children were administered the Wally Social Problems Test and the DeMoulin Self-Concept Development Scale, while the mothers completed the Parenting Attitudes Scale and the Demographic Information Form. The mediating role of self-esteem and self-efficacy in the relationship between parenting styles and children’s social problem-solving skills was examined using PROCESS MACRO. The results supported the proposed model, demonstrating that the impact of democratic parenting style on social problem-solving skills was partially mediated by self-concept, specifically self-esteem, as a parenting measure. These findings suggest that self-esteem is an essential individual characteristic to consider in relation to preschoolers’ social relationships, in addition to the influence of democratic parenting style behaviors.